2015
DOI: 10.1038/srep12956
|View full text |Cite
|
Sign up to set email alerts
|

An antenna model for the Purcell effect

Abstract: The Purcell effect is defined as a modification of the spontaneous emission rate of a quantum emitter at the presence of a resonant cavity. However, a change of the emission rate of an emitter caused by an environment has a classical counterpart. Any small antenna tuned to a resonance can be described as an oscillator with radiative losses, and the effect of the environment on its radiation can be modeled and measured in terms of the antenna radiation resistance, similar to a quantum emitter. We exploit this a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
179
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 181 publications
(188 citation statements)
references
References 74 publications
(166 reference statements)
5
179
1
2
Order By: Relevance
“…To simulate the nanoantenna consisting of 8 nanoparticles, located on the SiO 2 substrate with ε sub = 2.21, we utilize the commercial software CST Microwave Studio. To calculate the Purcell factor, the method based on the input impedance of a small (in terms of radiation wavelength) dipole antenna [39] has been applied. The corresponding results are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…To simulate the nanoantenna consisting of 8 nanoparticles, located on the SiO 2 substrate with ε sub = 2.21, we utilize the commercial software CST Microwave Studio. To calculate the Purcell factor, the method based on the input impedance of a small (in terms of radiation wavelength) dipole antenna [39] has been applied. The corresponding results are presented in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This method was shown to be applicable to the Purcellfactor calculation in a variety of frequency ranges, i.e., from radio to optics [55,56]. More importantly, this method can be applied to structures with complex geometry and finite dimensions, where analytic approaches do not work.…”
Section: Structures and Methodsmentioning
confidence: 99%
“…The Purcell effect is manifested in a modification of the spontaneous emission rate (Γ) of a quantum emit-ter induced by its interaction with inhomogeneous environment and is quantitatively expressed by the Purcell factor [114][115][116][117][118][119]. This modification is significant if the environment is a resonator tuned to the emission frequency.…”
Section: All-dielectric Nanophotonics Applicationsmentioning
confidence: 99%
“…These ideas were developed in the series of subsequent works [90,[92][93][94][95][96][97][98][99]. It has been demonstrated that the unique optical properties and low dissipative losses make dielectric nanoparticles perfect candidates for design of high-performance nanoantennas, low-loss metamaterials, and other novel all-dielectric nanophotonic devices.…”
Section: All-dielectric Nanophotonics Applicationsmentioning
confidence: 99%